PENGARUH VARIASI LAMA WAKTU KONTAK DAN BERAT TANAMAN APU-APU (Pistia stratiotes L.) TERHADAP KADAR TIMBAL PADA IRIGASI PERTANIAN - Rahayuningtyas, Indah; Wahyuningsih, Nur Endah; Budiyono, Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2018)
Lead is one of heavy metals in pesticides and 80% will be wasted into the environment, thus impact on ecology and human health. The results of the preliminary study of irrigation water in Desa Siwuluh, Kecamatan Bulakamba, Brebes contains lead  with an average level of 0,187 mg/l. It was signify that lead  in irrigation water has exceeded the quality standard of Peraturan Pemerintah Republik Indonesia No.82 Tahun 2001 which is 0.03 mg/l. One of the methods used to reduce lead levels is phytoremediation by using Apu-Apu (Pistia stratiotes L.). The purpose of this research to determine the effect of contact time variations (3 days, 5 days, and 10 days) and weight of plant (150 grams, 200 grams and 250 grams) Pistia stratiotes L. to reduce lead levels in irrigation water. This type of research was the design of quasi experimental. The population of this study was irrigation water of Desa Siwuluh, Kecamatan Bulakamba, Kabupaten Brebes with the grab sampling method. The sample used in this study was 150 liters for 9 treatments with 3 repetitions and 3 controls. The method of lead level examination uses the Atomic Absorption Spectophotometer (AAS). Data analysis used friedmann with level confidence 95%. The highest reduction in lead levels occurred in the 10-day contact time (100%) and there were no significant diffence in weight of water lettuce variation. The results showed that there was a significant difference lead levels in irigatiion water with tretment weight of apu-apu and contact time p-value=0,001 (p<0,05). The conclusion is Pistia stratiotes L. effective to reduced lead levels in irigation water in 10-day contact time.